Traditional Chinese Medicine nursing in prevention of pulmonary infection in patients with hypertensive cerebral hemorrhage (高血压脑出血患者预防肺部感染的中医护理探讨) - FU Jingna (付景娜); GENG Qingwen (耿庆文); HU Zhe (胡哲); SU Rong (苏容); GUO Haijiao (果海姣); ZHANG Bing (张兵) (中西医结合护理)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) nursing in prevention of pulmonary infection in patients with hypertensive cerebral hemorrhage. Methods Totally 120 patients with hypertensive cerebral hemorrhage were divided into control group (n = 60) and observation group (n = 60) according to different types of nursing care. Patients in the control group received routine care, and those in the observation group received TCM nursing on basis of routine care. The effective rate of nursing intervention between two groups was analyzed and compared. Results The total effective rate of nursing intervention in the observation group was higher than that in the control group (96. 67% vas. 73. 33%, P<0. 01). Conclusion In nursing management of patients with hypertensive cerebral hemorrhage, the TCM nursing intervention is potentially effective to prevent the pulmonary infection and improve the nursing efficiency. (目的 探讨高血压脑出血患者预防肺部感染的中医护理措施实施效果。方法 选取120例高血压脑出血患者为研究对象, 根据护理方法的不同分为对照组和观察组, 各60例。对照组采用常规护理, 观察组在对照组基础上增加中医护理干预。 评价2组护理干预效果。结果 观察组护理有效率96. 67%(58/60), 高于对照组的73. 33%(44/60), 差异有统计学意义(P＜0. 01)。结论 在高血压脑出血患者临床护理中增加中医护理干预, 能有效预防和控制肺部感染的发生, 护理效果明显。)